2011
DOI: 10.1039/c0dt00832j
|View full text |Cite
|
Sign up to set email alerts
|

Metallacrowns of Ni(ii) with α-aminohydroxamic acids in aqueous solution: beyond a 12-MC-4, an unexpected (vacant?) 15-MC-5

Abstract: Growing attention has been devoted in the recent years to a class of metallamacrocycles known as metallacrowns (MCs). They are structural analogues of crown ethers where the methylene bridges have been substituted by coordinative bonds formed by a transition metal ion ("ring" metal) and a nitrogen atom. The cavity of the metallacrown can accommodate an additional metal ion ("core" metal) either identical or different from the ring metal, thus forming a homo- or hetero-metallic MC. The most studied ring metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 49 publications
5
36
0
Order By: Relevance
“…A dissociative pathway would in fact go through the formation of an intermediate vacant 15-MC-5 containing five negative oxygen atoms in the cavity that are not bound to a core metal. This species, although found for Ni II , 50 has never been observed with Cu II and it is likely a high-energy species for this metal. 3,15 The dissociative mechanism results, therefore, in a high activation energy, which makes the associative (or interchange associative) pathway preferred over a dissociative substitution.…”
Section: ■ Discussionmentioning
confidence: 84%
“…A dissociative pathway would in fact go through the formation of an intermediate vacant 15-MC-5 containing five negative oxygen atoms in the cavity that are not bound to a core metal. This species, although found for Ni II , 50 has never been observed with Cu II and it is likely a high-energy species for this metal. 3,15 The dissociative mechanism results, therefore, in a high activation energy, which makes the associative (or interchange associative) pathway preferred over a dissociative substitution.…”
Section: ■ Discussionmentioning
confidence: 84%
“…The commonest structural types of hydroxamate metallacrowns are 9‐MC‐3, 12‐MC‐4, and 15‐MC‐5. The planar copper(II) and nickel(II) 12‐MC‐4 and 15‐MC‐5 complexes demonstrate stability in solutions under a range of conditions,, while the availability of vacancies in the coordination spheres of their metal ions (or potentially vacant positions occupied by labile solvent molecules) makes them promising candidates for use as building blocks for coordination polymers and supramolecular assemblies. Additional reasons for using this class of coordination compounds as building blocks are their interesting properties, such as ability for selective recognition of cations, anions, and molecules,, catalytic activity, non‐trivial magnetism,, , luminescence, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation concerning a study on the Ni(II)/ α-alaninehydroxamic acid (AlaHA) system, 36 very unexpectedly revealed that a vacant 15-MC-5 is formed under appropriate conditions and in the absence of a suitable core metal. A "vacant" 12-MC-4 complex is also formed, although it is not markedly stable.…”
Section: Introductionmentioning
confidence: 99%